Affinity switching of the LEDGF/p75 IBD interactome is governed by kinase-dependent phosphorylation - Sharma, Subhalakshmi; Čermáková, Kateřina; De Rijck, Jan; Demeulemeester, Jonas; Fábry, Milan; El Ashkar, Sara; Van Belle, Siska; Lepšík, Martin; Tesina, Petr; Duchoslav, Vojtěch; Novák, Petr; Hubálek, Martin; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Lens epithelium-derived growth factor/p75 (LEDGF/p75, or PSIP1) is a transcriptional coactivator that tethers other proteins to gene bodies. The chromatin tethering function of LEDGF/p75 is hijacked by HIV integrase to ensure viral integration at sites of active transcription. LEDGF/p75 is also important for the development of mixed-lineage leukemia (MLL), where it tethers the MLL1 fusion complex at aberrant MLL targets, inducing malignant transformation. However, little is known about how the LEDGF/p75 protein interaction network is regulated. Here, we obtained solution structures of the complete interfaces between the LEDGF/p75 integrase binding domain (IBD) and its cellular binding partners and validated another binding partner, Mediator subunit 1 (MED1). We reveal that structurally conserved IBD-binding motifs (IBMs) on known LEDGF/p75 binding partners can be regulated by phosphorylation, permitting switching between low- and high-affinity states. Finally, we show that elimination of IBM phosphorylation sites on MLL1 disrupts the oncogenic potential of primary MLL1-rearranged leukemic cells. Our results demonstrate that kinase-dependent phosphorylation of MLL1 represents a previously unknown oncogenic dependency that may be harnessed in the treatment of MLL-rearranged leukemia.
Keywords: protoonkogenní protein MLL; mediátorový komplex - podjednotka 1; nádorové buněčné linie; phosphorylation; Phosphorylation; HIV Integrase; HIV-integrasa; adaptorové proteiny signální transdukční; Amino Acid Motifs; Cell Line, Tumor; protein–protein interactions; Transcription Factors; aminokyselinové motivy; disordered proteins; Mediator Complex Subunit 1; transkripční faktory; leukemia; Adaptor Proteins, Signal Transducing; Humans; HIV; LEDGF/p75; histonlysin-N-methyltransferasa; Histone-Lysine N-Methyltransferase; fosforylace; Myeloid-Lymphoid Leukemia Protein; lidé